2014
DOI: 10.1073/pnas.1319397111
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling mediates homeostatic maturation of new T cells

Abstract: Interleukin (IL)-7 is critical for the maintenance of the peripheral T-cell compartment of the adaptive immune system. IL-7 receptor α ( IL-7Rα) expression is subject to developmental regulation and new T cells induce expression as they leave the thymus, which is essential for their long-term survival. It is not understood how this expression is regulated. Here, we identify a role for the Nuclear Factor κ-B (NF-κB) signaling pathway in controlling expression of IL-7Rα in new T cells. Perturbations to NF-κB sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 42 publications
7
58
0
1
Order By: Relevance
“…In contrast, our findings suggest that NF-κB-dependent survival of naïve T cells relies, at least in part, on Bcl-2 upregulation on IL-7 exposure. Supporting our results, Silva et al (33) recently reported that IKKβ is required for IL-7Rα expression and homeostatic proliferation. Together with our findings, both studies define a role for NF-κB in the control of naïve T cells homeostasis in both lymphoreplete and lymphopenic hosts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, our findings suggest that NF-κB-dependent survival of naïve T cells relies, at least in part, on Bcl-2 upregulation on IL-7 exposure. Supporting our results, Silva et al (33) recently reported that IKKβ is required for IL-7Rα expression and homeostatic proliferation. Together with our findings, both studies define a role for NF-κB in the control of naïve T cells homeostasis in both lymphoreplete and lymphopenic hosts.…”
Section: Discussionsupporting
confidence: 92%
“…As in mice, de novo IL-7Rα reexpression in human T cells was impaired by pharmacological inhibition of NF-κB following exposure to IL-7. By contrast, deletion of IKKβ in mouse postthymic T cells did not affect constitutive levels of IL-7Rα (33), suggesting that in mature T cells NF-κB may be required for de novo IL-7Rα reexpression but not for its physiological maintenance. TNF stimulation has been reported to up-regulate IL7R mRNA in human HeLa cells in an NF-κB-dependent manner (43), and chromatin immunoprecipitation and sequencing data from the ENCODE project revealed RelA binding to the homologous IL7R ECR2 sequence in human lymphoblastoid cell lines (44).…”
Section: Discussionmentioning
confidence: 79%
“…The number of peripheral F5 T cells in such chimeras represents the equilibrium between thymic generation of new F5 T cells and loss of peripheral mature T cells in the presence of low Zap70 expression level. Recent thymic emigrants (RTE) in F5 mice can be readily identified by expression profile of HSA hi CD45RB lo Qa2 lo (31). In F5 TetZap70 chimeras fed dox, a higher proportion of F5 T cells expressed HSA, and this population was reduced when mice were taken off Dox for 7 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During their maturation, RTE express lower IL-7Rα than mature T cells (32) and this contributes to reduced survival and LIP by RTE (31). In F5 mice, F5 T cells upregulate IL-7Rα expression following egress from the thymus therefore for a time, RTE in F5 mice express low levels of IL-7Rα compared with mature naive F5 T cells (31). High levels of IL-7 in vivo can promote T cell survival in the absence of Zap70 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation